2012
DOI: 10.2131/jts.37.235
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges in breast cancer patients who underwent chemotherapy

Abstract: -The study aimed to determine the effects of cytostatic and genotoxic drugs used to treat breast cancer on sister chromatid exchange (SCE). SCE values were examined in 25 female patients with breast cancer in pre-treatment, treatment process and remission period as well as in 22 nonsmoker women via peripheral blood culture technique. The SCE values of patient and control group were analyzed via "Mann-Whitney U test". Whilst SCE values of patient group were 8.25 ± 3.67, 10.19 ± 2.95 and 11.52 ± 3.33 in pre-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Moreover, in comparison to pre-treatment specimens, post-treatment blood samples showed significantly reduced PRI values (P < 0.0001; Table 3). Similar results have been obtained by others (Kopjar et al, 2007;Tekcan et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, in comparison to pre-treatment specimens, post-treatment blood samples showed significantly reduced PRI values (P < 0.0001; Table 3). Similar results have been obtained by others (Kopjar et al, 2007;Tekcan et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The FAC protocol was shown to be the most genotoxic of those studied (Kopjar et al, 2007). Tekcan et al (2012) also recorded a significantly augmented SCE rate in post-chemotherapy peripheral blood lymphocytes. In their investigation, patient groups were treated with AC, 5-fluorouracil + epirubicin + cyclophosphamide, or epirubicin + cyclophosphamide.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since age and genomic instability are associated with failure of DNA repair and accumulation of DNA damage in the genome, many authors have evaluated the association between SCE frequency and age, but data in the literature are controversial (4,14,19,(22)(23)(24). In accordance with other studies, we found no correlation between age and SCE frequency, either in familial or in sporadic patients (4,14).…”
Section: Familial N=22supporting
confidence: 86%
“…Increased genetic susceptibility could be associated with genomic instability, which could lead to chromosomal breakage. Sister chromatid exchange (SCE) is an error-free recombination mechanism, defined as a symmetrical exchange between portions of apparently homologous sister chromatids (4). Although little is known about its molecular basis, these exchanges presumably involve DNA breakage and subsequent reunion of newly synthesized DNA chains during replication (5,6).…”
Section: Introductionmentioning
confidence: 99%